CONSTRUCTING CONSUMER EMPOWERMENT THROUGH FINANCIAL FLEXIBILITY: A CRITICAL DISCOURSE ANALYSIS OF KREDIVO’S PAYLATER ADVERTISEMENT - Meliyana (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This study critically examines how Kredivo’s Paylater advertisement constructs consumer empowerment through the discourse of financial flexibility. By using Norman Fairclough’s three-dimensional Critical Discourse Analysis (CDA) and Michel Foucault’s concept of governmentality, the research investigates how language and visuals in the ad reframe borrowing not as a sign of financial desperation but as rational and strategic behavior. A qualitative critical method is applied to six selected captions and visuals from Kredivo’s advertisements on YouTube and Instagram, chosen for their rich promotional language and symbolic imagery. Thus, findings reveal that phrases like “Pake Paylater bukan karena gak ada duit, tapi belajar menghitung” present debt as a sign of intelligence and financial literacy. Other slogans such as “1 menit cair” and “cicilan tanpa kartu kredit” emphasize speed, convenience, and inclusivity, while simultaneously obscuring structural financial risks and the potential for over-indebtedness. Therefore, these representations position consumers as self-disciplined, entrepreneurial individuals aligned with neoliberal ideals of personal responsibility and financial self-management. By portraying borrowing as empowerment, the discourse shifts accountability for financial outcomes onto the individual and this study contributes to advertising discourse analysis by focusing on fintech ads, exposing how such campaigns reshape consumer identities and normalize debt within Indonesia’s digital economy.